Literary Journalism as a Discipline: Tom Wolfe and Beyond - Keeble, Richard Lance (Brazilian journalism research, 2018)
The publication of Tom Wolfe’s The New Journalism in 1973 was the seminal moment for the formation of literary journalism as an academic discipline. Wolfe both celebrated the work of more than 20 contemporary journalists whom he dubbed “new journalists” and identified the main elements of their writings. But his concentration on their individual techniques (which has proved so influential in the development of literary journalism in higher education) crucially marginalized consideration of such elements as ideology and political economy, and promoted a problematic form of cultural elitism. In exploring the political economy of literary journalism, this paper will identify similarities between the formation of English as an academic discipline in the UK in the 18th and 19th centuries and the launch of literary journalism in the US in the 1970s and 1980s. And to help literary journalism expand its horizons and draw inspiration from a much wider range of academic disciplines, the paper will argue for its radical democratization. A publicação do livro de Tom Wolfe The New Journalism, em 1973, foi o momento fundamental para a formação do jornalismo literário como disciplina acadêmica. Wolfe celebrou o trabalho de mais de 20 jornalistas contemporâneos, apelidando-os de “novos jornalistas” e identificando seus principais elementos de escrita. Contudo, sua concentração em técnicas individuais (que se mostrou tão influente no desenvolvimento do jornalismo literário no ensino superior) decisivamente segregou a consideração de elementos como ideologia e economia política, promovendo uma forma problemática de elitismo cultural. Ao explorar a economia política do jornalismo literário, este artigo identifica semelhanças entre a formação do inglês como disciplina acadêmica no Reino Unido nos séculos XVIII e XIX e o lançamento do jornalismo literário nos Estados Unidos nos anos 1970 e 1980. E para ajudar o jornalismo literário a expandir seus horizontes e a inspirar-se em uma gama muito mais ampla de disciplinas acadêmicas, o artigo argumenta a favor de sua democratização radical. La publicación del libro The New Journalism de Tom Wolfe, en 1973, fue el momento fundamental para la formación del periodismo literario como disciplina académica. Wolfe celebró el trabajo de más de 20 periodistas contemporáneos a los que denominó “nuevos periodistas” e identificó los principales elementos de sus escritos. Pero su concentración en sus técnicas individuales (que ha demostrado ser tan influyente en el desarrollo del periodismo literario en la educación superior) marginó de manera crucial la consideración de elementos como la ideología y la economía política, y promovió una forma problemática de elitismo cultural. Al explorar la economía política del periodismo literario, este trabajo identificará similitudes entre la formación del inglés como disciplina académica en el Reino Unido en los siglos XVIII y XIX y el lanzamiento del periodismo literario en los Estados Unidos en los años setenta y ochenta. Y para ayudar a que el periodismo literario amplíe sus horizontes y se inspire en una gama mucho más amplia de disciplinas académicas, el periódico defenderá su radical democratización.